Caracterização de isolados de leishmania (leishmania) infantum resistentes ao antimônio: mecanismo de resistência a droga e sua relação com a atividade microbicida de macrófagos e neutrófilos - Magalhães, Lucas Sousa (2020)
The visceral leishmaniasis is a serious infectious disease, endemic in Brazil and caused by Leishmania (Leishmania) infantum parasites. The microbicides mechanisms of macrophages and neutrophil are related to control of the parasites. The chemotherapy with antimonial compounds is the main form of disease control. In the last years innumerous cases of treatmentrelapse patients and drug-resistant parasites were described. Besides that, few studies look for investigate the drug-resistance mechanisms in parasites from Americas and principally are few the researches who seek investigate the relationship between drug resistance mechanisms and the host immune system. In this way, the present work aims to describe the mechanism of resistance to antimony in L. (L.) infantum isolates and the relationship of drug resistance with the infection of neutrophil and macrophages. Initially, was observed that drug-resistant parasites have higher levels of thiol compounds, an essential molecule present in natural antioxidants. The blockade of thiol synthesis in drug-resistant isolates increase the sensibility of these parasite to antimony and reduced the buffering capacity of reactive oxygen species. Next, the neutrophils infection with antimony-resistant and antimony-sensitive isolates show that no differences in the percentage of infected cell, intensity of parasitism or in the production of reactive oxygen species. Moreover, was evaluated if the treatment of promastigotes with inhibitor of thiol synthesis interfere in the infection of macrophages, where observed a higher control of parasite load and dissemination. The effect was observed to when the thiol synthesis blockade was made during 24h of infection. Both results were related to higher synthesis of TNF-α. At last, since the blocking of drug-resistance mechanism enhances the parasitism control e production of pro-inflammatory cytokine, was evaluated if the macrophage activation by IFN-γ+LPS, soluble CD40L and anti-IL-10, could control the infection of antimony-resistant parasites. In general, all treatments enhance the control of antimony-resistant parasites and stimulate the release of pro-inflammatory cytokines, classically associated to microbicidal mechanisms. Together, the data showed here demonstrated that higher levels of thiol in antimony-resistant parasites are associated to drug resistance and cross-resistance to microbicidal effectors. Additionally, the resistance mechanism in L. (L.) infantum isolates is associated to the modulation of macrophage infection, and it is controlled by the activation of pro-inflammatory response. These data highlight the necessity of better understanding the antimony-resistant parasites interaction with the immune system, and the search of alternative therapeutics which contributes in the complete clearance of parasites and allow a better clinical evolution and cure of the patients.